fMRI Revealed Reduced Amygdala Activation after Nx4 in Mildly to Moderately Stressed Healthy Volunteers in a Randomized, Placebo-Controlled, Cross-Over Trial - Herrmann, Luisa; Vicheva, Petya; Kasties, Vanessa; Danyeli, Lena V.; Szycik, Gregor R.; Denzel, Dominik; Fan, Yan; Meer, Johan Van der; Vester, Johannes C.; Eskoetter, Herbert; Schultz, Myron; Walter, Martin (Scientific reports, 2020)
Social stress contributes to major societal health burdens, such as anxiety disorders and nervousness. Nx4 has been found to modulate stress responses. We investigated whether dampening of such responses is associated with neuronal correlates in brain regions involved in stress and anxiety. In a randomized, placebo-controlled, double-blind, cross-over trial, 39 healthy males took a single dose (three tablets) of either placebo or Nx4, 40 to 60 minutes before an fMRI scan session. We here report on drug effects on amygdala responses during a face-matching task, which was performed during a complex test battery further including resting-state brain connectivity and a social stress experiment. The first of the Primary Outcomes, defined in a hierarchical order, concerned reduced amygdala effects after intake of verum compared to placebo. We found a statistically significant reduction in differential activations in the left amygdala for the contrast negative faces versus forms during verum versus placebo condition. Our results indicate that effects of Nx4 can be monitored in the brain. Previously noted effects on stress responses may thus be modulated by affective brain regions including the amygdala.